Plaque Rupture-Induced Myocardial Infarction and Mechanical Circulatory Support in Alpha-Gal Allergy - Sohab S. Radwan; Gauravpal Gill; Amre Ghazzal; Awais Malik; Christopher Barnett (Case Reports in Cardiology)
Alpha-gal (AG) allergy is an IgE-mediated allergic reaction to galactose-alpha-1,3-galactose found in mammalian meat. Heparin, being derived from porcine intestinal tissue, may have a degree of cross-reactivity with AG antigen and thus place patients at risk for allergic and even anaphylactic reactions. This is especially important in patients with myocardial infarction (MI) and mechanical circulatory support, such as a left ventricular assist device (LVAD), since anticoagulation is immediately required. Therefore, individualized assessment and preoperative planning is needed regarding the use of heparin vs. nonheparinoid products in such a population.